P1082Validation of cardiologist-created, audiovisual education delivered via smart devices while awaiting outpatient consultation: optimising atrial fibrillation management through shared decision making. (18th June 2020) - Kovoor, J G; Mcintyre, D; Chik, W W B; Chow, C K; Thiagalingam, A
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia worldwide and its management requires numerous complex decisions shared between patients and their treating cardiologist. However, apart from the restricted time within each consultation, there is limited opportunity to educate patients for optimising the shared decision making that can subsequently impact the effectiveness of their management. A relatively untested opportunity for education is while patients are awaiting cardiology outpatient consultation. This could be in part due to the lack of availability of educational material that is suitable for both patient management and satisfaction, or that the development process is often too time or resource-heavy for the respective cardiologist. Audiovisual educational material created by the cardiologist could potentially be better received by patients while awaiting outpatient consultation. Purpose: To evaluate the effectiveness and efficiency of a cardiologist-created, audiovisual educational module in facilitating shared decision making for the management of AF. Methods: The cardiologist developed 4 educational videos on AF that aimed to enhance patient knowledge for the following topics: (1) What is AF?, (2) AF Management, (3) Stroke risk and anticoagulation, and (4) Lifestyle modification. The videos were then combined into a web-based audiovisual module where they were viewed sequentially and accompanied by questions gauging patient experience. The module was delivered using Quick Response (QR) code scanning on smart devices to 115 patients with AF in the waiting room prior to cardiologist consultation. Feedback was recorded on 5-point Likert Scales or Visual Analogue Scales (VAS). Results: Each video took an average of 3 minutes and 42 seconds for the cardiologist to record using minimal resources comprising of a smart device and a desktop computer for the cardiologist-narrated audiovisual presentation. On the Likert scales, 96.4% of responders were "very satisfied" with the individual videos, with only 0.8% of responses conveying dissatisfaction. The VAS ratings (0-100) were: Improving peri-consultation anxiety 89.93 +/- 9.62; Improving the patient's decision making 85.86 +/- 16.71; Improving likelihood of long-term treatment adherence 87.30 +/- 12.27; Beneficial effect on patient experience from the cardiologist's narration in the educational module 86.51 +/- 14.86. Conclusions: The audiovisual educational module was created by the cardiologist in a time and resource-efficient manner. Patients responded positively to both the cardiologist's narration and the content of the AF-specific videos. This approach was not only a beneficial utilisation of the patient's waiting time prior to outpatient consultation, but also a simple, time and resource-efficient way that cardiologists themselves can provide patient education, and by extension optimise shared decision making in the management of AF.